Exploring the Integration of AI in Public Library Services - Rahmani, Mehdi (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore the extent of AI integration in public libraries, identify the benefits and challenges faced by libraries in adopting AI technologies, and propose strategies for effective implementation. It seeks to provide a comprehensive overview of the current state of AI applications in library services and offer insights into future trends. Employing a qualitative research design, this study collected data through semi-structured interviews with 29 participants, including librarians, IT specialists, library managers, and library users. Thematic analysis was used to analyze the interview transcripts, allowing for the identification of key themes related to AI integration in public libraries. Four main themes emerged from the data: AI Applications, Challenges and Responses, Service Evolution, and Adoption and Integration. AI Applications were categorized into User Interaction, Operational Tasks, and Learning Tools, highlighting AI's role in enhancing service delivery and operational efficiency. Challenges and Responses revealed technical barriers, staff training needs, user engagement issues, and financial constraints as significant obstacles to AI adoption. Service Evolution demonstrated AI's impact on information accessibility, user experience, operational improvements, and community outreach. Adoption and Integration emphasized the importance of strategic planning, community involvement, and policy compliance in successfully integrating AI into library services. The study concludes that while AI offers substantial opportunities to redefine public library services, its successful integration requires addressing technical, ethical, and financial challenges. Libraries must focus on staff training, ethical AI use, and strategic planning to fully realize the benefits of AI. Future research should aim to quantify the impact of AI on library services and explore innovative AI applications in diverse library contexts.